Errors Classification in Google Translate when Rendering Batak Cultural Terms into English - Sunarti Desrieny Tambunan (Asosiasi Dosen Muda Indonesia, 2026)
This research aims to identify the errors that Google Translate make when rendering Batak Toba culturally specific terms into English in five selected articles. Qualitative research was applied to analyze the translated terms from the Batak language into English. The result showed that there were 3 data of orthography (errors in capitalization (2), and spelling (1)), 1 data of lexis level (errors in addition (1)), 4 data of semantic level (errors in choice (3) and confusion of senses (1)), 8 data of discourse to analyze the translation of Batak terms level (under should not be translated (7)). Thus, the total number of data errors found was 15. No data were found at the grammar level.